2010
DOI: 10.3109/10641960903254471
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Parathyroidectomy on Hypertension Prevalence and Circadian Blood Pressure Profile in Primary Hyperparathyroidism

Abstract: Our aims were to evaluate the prevalence and outcome of hypertension in patients with primary hyperparathyroidism (PHPT), previously and after follow-up of parathyroidectomy. A group of 46 consecutive patients with sporadic PHPT due to adenoma undergoing surgery were followed an average of 3.5 years (range 36 to 53 months). In 16 nonselected, consecutive parathyroidectomized patients, with normalized biochemical measurements, circadian rhythm of blood pressure was evaluated with ambulatory blood pressure monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 27 publications
1
17
0
2
Order By: Relevance
“…In the present study the incidence of HA was 55%. Other studies confirm this tendency, and in one report the HA incidence was even higher (81%) [35][36][37]. It has also been directly observed that PTH infusion results in HA in healthy subjects [38].…”
Section: Cardiovascular Effectssupporting
confidence: 60%
See 1 more Smart Citation
“…In the present study the incidence of HA was 55%. Other studies confirm this tendency, and in one report the HA incidence was even higher (81%) [35][36][37]. It has also been directly observed that PTH infusion results in HA in healthy subjects [38].…”
Section: Cardiovascular Effectssupporting
confidence: 60%
“…It has also been directly observed that PTH infusion results in HA in healthy subjects [38]. Still, data describing the impact of surgical PHPT treatment on HA and the circadian rhythm of blood pressure are not consistent [36,37].…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…Hypertension secondary to pHPT is still being debated [22] . The 54.1% incidence rate of hypertension in pHPT is within the range of 20-69% reported in various studies [5,23,24] . This large variation in reported incidence could be due to variations between different authors due to differences in blood pressure measurement criteria of hypertension and different patient characteristics.…”
Section: Discussionmentioning
confidence: 65%
“…Limited data exist on the effect of PTx on blood pressure in patients with mild PHPT; blood pressure was reduced one year after surgical intervention in one study (38) while it remained stable after 6 months in another investigation (39,40). It should be noted that the only randomized two-year duration study in mild PHPT patients showed neither benefit after PTx nor a deleterious effect on blood pressure with conservative management (41).…”
Section: Hypertensionmentioning
confidence: 99%